Challenges of Developing Human Resources In Education During The Post-Covid-19 Recovery Period - zubaidi, zubaidi; Dermawan, Oki (JIEM (Journal of Islamic Education Management), 2024)
Abstract. Teachers are the most important element in the world of educators who cannot be separated in the transformation of knowledge. There is a problem when a teacher in transforming education does not have adequate abilities, of course there will be obstacles where the learning process does not run optimally. Moreover, during the recovery period from the Covid 19 pandemic, all activities rely on digitalization technology, which is currently running on the industrial revolution 4.0 and civil society 5.0 where a teacher must master technology or at least be able to adapt to the digital world.Keywords: world, education, digitalGuru adalah elemen terpenting dalam dunia pendidik yang tidak dapat terpisahkan dalam transformasi pengetahuan. Terdapat permasalahanÂ  manakala seorang guru dalam mentransformasi pendidikan tidak memiliki kemampuan yang memadai, tentu akan terjadi kendala di mana proses pembelajaran tidak berjalan dengan maksimal. Terlebih di masa pemulihan pandemi covid 19 semua kegiatan mengandalkan teknologi digitalisasi, yang saat ini berjalan pada revolusi industri 4.0 dan civil society 5.0 di mana seorang guru harus menguasai teknologi atau setidaknya mampu beradaptasi dengan dunia digital..Kata kunci: dunia, pendidikan, digital